2016
DOI: 10.3892/mmr.2016.5618
|View full text |Cite
|
Sign up to set email alerts
|

Potential fluid biomarkers for pathological brain changes in Alzheimer's disease: Implication for the screening of cognitive frailty

Abstract: Cognitive frailty (CF) overlaps with early neuropathological alterations associated with aging-related major neurocognitive disorders, including Alzheimer's disease (AD). Fluid biomarkers for these pathological brain alterations allow for early diagnosis in the preclinical stages of AD, and for objective prognostic assessments in clinical intervention trials. These biomarkers may also be helpful in the screening of CF. The present study reviewed the literature and identified systematic reviews of cohort studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 114 publications
1
18
0
2
Order By: Relevance
“…In addition, pathway enrichment analysis was conducted on these genes and showed that focal adhesion, TGF-β signaling pathway, and MAPK signaling pathway were significantly enriched by up-regulated genes, and synapse transmission, neuronal system, and calcium signaling pathway were significantly enriched by down-regulated genes [complete list shown in our previous study (27)]. These pathways are consistent with previous observations that AD is associated with neuronal damage and apoptosis, synaptic dysfunction, neuronal activity alteration, blood brain barrier dysfunction, neuro inflammation, oxidative stress, mitochondrial function and aberrant lipid metabolism (28). Therefore, these differentially expressed genes are speculated to be associated with AD pathogenesis.…”
Section: Resultssupporting
confidence: 87%
“…In addition, pathway enrichment analysis was conducted on these genes and showed that focal adhesion, TGF-β signaling pathway, and MAPK signaling pathway were significantly enriched by up-regulated genes, and synapse transmission, neuronal system, and calcium signaling pathway were significantly enriched by down-regulated genes [complete list shown in our previous study (27)]. These pathways are consistent with previous observations that AD is associated with neuronal damage and apoptosis, synaptic dysfunction, neuronal activity alteration, blood brain barrier dysfunction, neuro inflammation, oxidative stress, mitochondrial function and aberrant lipid metabolism (28). Therefore, these differentially expressed genes are speculated to be associated with AD pathogenesis.…”
Section: Resultssupporting
confidence: 87%
“…This makes urine ideal for biomarker discovery and screening tests [ 5 ]. However, studies on urinary AD biomarkers are limited [ 6 ], with only a few reports on protein biomarkers [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biomarkers derived from cerebrospinal fluid (CSF) and peripheral blood have been developed for the purpose of early AD symptom detection. Among which, CSF-based biomarkers have been designed for AD detection dependent on the alteration of neuron pathological lesions, including total tau protein (T-tau, reflecting the intensity of neuro axonal degeneration), phosphorylated tau (P-tau, correlating with tangle pathology) and the ratio of Aβ42/40 (correlating inversely with the plaque pathology) as previously reported [23, 24]. …”
Section: Introductionmentioning
confidence: 99%